An Analysis of Total Water Storage Changes Obtained from GRACE FO Observations over the Venezia Islands Area Supported with Additional Data - Biryło, Monika; Rzepecka, Zofia (Geomatics and Environmental Engineering, 2021)
The Venezia Islands are a very special area from the hydrological point of view due to its water mass changes. Regular floods results in the need for the regular monitoring of water mass changes. For this purpose, a Gravity Recovery and Climate Experiment mission (GRACE) can be used as a source of data. The aim of the paper is to compare the latest results of the new GRACE FO observations. The comparisons were carried out all over Venezia Island using the L3 level, RL06 release data obtained with spherical harmonics degree and order extension of up to 120, by the three most important computational centres: JPL, GFZ, CSR. Results are compared to an average month values of precipitation and evapotranspiration and tide gauge data in the nearby area. Based on the research, no dependence between TWS and evapotranspiration and evapotranspiration change were found.